Analysis of Sharia Investment and its Influence on Muslim Investors’ Decision-Making in Indonesia - Siva Alzaneta (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Indonesia, as the country with the largest Muslim population in the world, has enormous potential for developing Sharia-compliant investments. Sharia investment is a capital investment system based on Islamic principles, free from riba (usury), gharar (gharar), and maysir (gambling), and emphasizes the values ​​of justice, transparency, and sustainability in economic activities. Sharia investment is expected to provide an alternative financial system that is not solely oriented towards financial gain but also aligns with the ethical and social values ​​of the Muslim community. This article aims to analyze the concept of Sharia investment and examine the factors influencing Muslim investors' decisions in selecting Sharia-compliant investment instruments in Indonesia. The research method used is a qualitative descriptive approach through a literature review of recent scientific journals, reference books, and official reports from Sharia financial institutions and regulators. The study results indicate that Sharia financial literacy plays a significant role in shaping investors' understanding and attitudes toward Sharia investment. Furthermore, risk perception, return levels, and trust in Sharia financial institutions and Sharia supervision have been shown to significantly influence investment decisions. These findings underscore the importance of improving education, transparency, and institutional strengthening to encourage sustainable growth of sharia investment in Indonesia.